Analisis studi kelayakan bisnis pada industri perbankan: Studi pada bank syariah indonesia KCP nganjuk ahmad yani - Styawati, Diyah Ajeng (Maliki Interdisciplinary Journal, 2025)
A business feasibility study is a crucial step in ensuring the success of establishing a branch of Bank Mega Syariah in Malang City. This city was chosen for its significant potential, supported by its education, tourism, trade sectors, and dynamic SMEs, as well as a majority Muslim population with a strong awareness of Sharia principles. This study analyzes legal, market and marketing, environmental, technical and technological, management and human resources, financial, and environmental impact (AMDAL) aspects to determine feasibility and the best strategies. The analysis results indicate that Bank Syariah Indonesia (BSI) has excelled in various aspects, particularly in legal compliance, environmental management, marketing strategies, technological readiness, and organizational management. However, there is room for improvement in financial aspects and human resource management. Overall, this strong foundation supports BSI in competing in both national and global Islamic banking sectors, contributing to financial inclusion and sustainability.